2015
DOI: 10.1097/aln.0000000000000759
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Crossover Study Comparing a Novel Needle Guidance Technology for Simulated Internal Jugular Vein Cannulation

Abstract: This real-time needle guidance technology (eZono) shows significant improvement in needle accuracy and cannulation time during simulated IJ vein puncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…Posterior wall injuries occurred in 71% of procedures using the navigation system and 71% using the free-hand technique. These results are different from those reported in the literature [ 6 ]. Further evaluation identified that the difference between our pilot study and previous results revealed that the authors used a shallow angle of approach for the needle.…”
Section: Introductioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Posterior wall injuries occurred in 71% of procedures using the navigation system and 71% using the free-hand technique. These results are different from those reported in the literature [ 6 ]. Further evaluation identified that the difference between our pilot study and previous results revealed that the authors used a shallow angle of approach for the needle.…”
Section: Introductioncontrasting
confidence: 99%
“…There are no studies which compare different puncture angles. The method described by Auyong et al used a slightly shallower insertion angle compared to the ASE and SCA recommended technique [ 6 ]. We performed a power analysis to determine an order of magnitude result.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…) . Inexperienced participants using the Ezono 4000 (Ezono AG, Jena, Germany) needed fewer out‐of‐plane attempts, shorter procedure times and made significantly less posterior wall and carotid artery punctures in simulated internal jugular vein cannulation . A recently developed prototype by General Electric (Wisconsin, USA) uses passive magnetic characteristics of commercially available needles, omitting the magnetisation procedure and, thus, improving workflow.…”
Section: Resultsmentioning
confidence: 99%